UJI RESIDU BEBERAPA BAHAN AKTIF PEPTISIDA TERHADAP PARASITOID TELUR Trichogramma sp. (Hymnoptera : Trichogramatidae) DI LABORATORIUM - Irawan, Maya Novita Sari; Kuswardani, Retna Astuti; sartini, Sartini (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2017)
This research aims to study was to determine the effect of various types of active ingredient on mortality Trichogramma sp. In the imago stadia and look for a safe pepticide for Trichogramma sp. In the imago and praimago stadia. Research method using experimental method. Test of pepticide effect on pre-epochal mortality and imago Trichogramma sp. Using the fress method of contact residue. The study was prepared based on Completely Randomized Design with 2 factors and 2 replications. The first factor was the active ingredient of pepticide consisting of 10 treatments namely Lamda Silahotrin 25 gr /L (P1), Dimehipo 400 gr/L (P2), Isoprophilamine Glifosat 480 g/L (P3), Brodifakum 0.005% (P4) , Methyl metsulfuron 20.05% (P5), Triadimefon 200 gr/L (P6), Sipermetrin 50 gr/L (P7), Propiconazole 125 g / L and Tricyclazole 400 gr / L (P8), Cypermethrin 113 g / L ( P9), Annonain (P10). The second factor was the concentration of pesticide (K) consisting of 3 treatments, namely 0.5 ml/L (K1), 1ml / L (K2), 1.5ml/L (K3). The results showed that the provision of various active ingredients of pesticide had a significant effect on egg parasitoid morality Trichogramma sp. On imigo stadia at 12 hours After application, 24 hours After application and 36 hours After application. In praimigo stadia provide a safe pesticide active ingredient on the 12 hours imagion stage After application. The best treatment on P3k3 with an emerge of 79.3%.